ISSR molecular markers and anatomical structures can assist in rapid and directional screening of cold-tolerant seedling mutants of medicinal and ornamental plant in Plumbago indica L. - Li, Yirui; Cheng, Xu; Lai, Junlin; Zhou, Yunzhu; Lei, Ting; Yang, Lijuan; Li, Jiani; Yu, Xiaofang; Gao, Suping (Frontiers in Plant Science, 2023)
Plumbago indica L. is a perennial herb with ornamental and anticancer medicinal functions widely distributed in the tropics. It is affected by temperature and cannot bloom normally in colder subtropical regions, which seriously affects its ornamental value. To create low-temperature resistance mutants and enrich new germplasm resources, this study used tissue culture and chemical reagent (0.5 mmol/L NaN3) and low-temperature stress (0°C, full darkness for 48h) induction to target and screen for cold-resistance mutants. The results showed that the ISSR band polymorphism ratio of the 24 suspected mutant materials was 87.5%. The DNA profiles of the 9 mutants initially identified were altered. The content of plumbagin in the stems and leaves of the mutants was examined, and it was found that the accumulation in the leaves of the mutant SA24 could be as high as 3.84 times that of the control, which was 0.5991%. There were significant differences in the anatomical structures of roots, stems and leaves. The mutants mostly exhibited reduced root diameter (only 0.17-0.69 times that of CK), increased stem diameter (up to 2.19 times that of CK), enlarged mesophyll cells, increased thickness (up to 1.83 times that of CK) and high specificity, which are thought to be important for the different cold resistance obtained by the mutants. In the cold resistance experiment, four cold-tolerant mutants were successfully screened according to their morphological characteristics and physiological indexes, and the mutagenesis efficiency could be as high as 2.22% and did not affect the accumulation of plumbagin in their stems and leaves, even higher than CK. The responses of the screened mutants SA15, SA19, SA23 and SA24 to low temperature showed slower leaf wilting, higher light energy conversion efficiency, less accumulation of MDA content, increased enzymatic activities of antioxidant enzymes (SOD, CAT, POD) and more accumulation of soluble sugars and proline content. These characteristics are consistent with the response of cold-resistance plants to low temperatures. The cold- resistance mutants cultivated in soil were observed of agronomic and ornamental traits for one year, mainly manifested as delayed flowering and delayed entry into the senescence stage. This study provides a more rapid and accurate technique for identifying and screening cold-tolerant mutants, and lays the foundation for future experiments on the creation of new cold-resistant varieties.